Fixed points of log-linear discrete dynamics - Ken Sawada; Yoshio Togawa (Discrete Dynamics in Nature and Society)
In this paper we study the fixed points of the Log-linear discrete dynamics. We show that almost all Log-linear dynamics have at most two fixed points which is a generalization of Soni's result.